2013
DOI: 10.1103/physrevb.88.245401
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-matched versus lattice-mismatched models to describe epitaxial monolayer graphene on Ru(0001)

Abstract: Monolayer graphene grown on Ru(0001) surfaces forms a superstructure with periodic modulations in its geometry and electronic structure. The large dimension and inhomogeneous features of this superstructure make its description and subsequent analysis a challenge for theoretical modeling based on density functional theory. In this work, we compare two different approaches to describe the same physical properties of this surface, focusing on the geometry and the electronic states confined at the surface. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…The second approach (which is more often used) employs a much smaller supercell with stretched lattice constant of graphene (to match the Ru (0001) lattice). [15][16][17] Previous studies have convincingly shown that although the second approach (the stretched model) neglects the long-range lattice variation (the moiré pattern), it does generate essentially the same electronic properties of the system as those obtained from the first approach, therefore can correctly describe the interaction between graphene and Ru (0001) and are good for further analysis.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The second approach (which is more often used) employs a much smaller supercell with stretched lattice constant of graphene (to match the Ru (0001) lattice). [15][16][17] Previous studies have convincingly shown that although the second approach (the stretched model) neglects the long-range lattice variation (the moiré pattern), it does generate essentially the same electronic properties of the system as those obtained from the first approach, therefore can correctly describe the interaction between graphene and Ru (0001) and are good for further analysis.…”
Section: Resultsmentioning
confidence: 94%
“…Density functional theory (DFT)-based computational modeling is the commonly used theoretical tool to understand physical and chemical properties of Ru (0001)-supported graphene. [15][16][17] In literature, two different types of DFT-based approaches have been used. The first one uses a very large supercell (e.g., 11 × 11 graphene unit cells) 17 to describe the so-called moiré pattern originated from the lattice mismatch between graphene and Ru.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of hybridization of the first is tailored by choosing a specific metal substrate. For G/Ru(0001), the strong hybridization with the substrate d bands opens a gap of about 2 eV in the graphene π bands just below E F [62,63]. This gap limits the hybridization between Co and graphene orbitals and preserves a largely unscreened Coulomb interaction.…”
Section: Fig 3 (Color Online) Magnetization Curve Of Comentioning
confidence: 99%
“…However, if the interface cell is large, the atomic bonding configurations will often vary considerably over the cell, so that in some parts of the cell favorable bonding configurations are obtained but in other parts not. Overall this leads to weaker bonding [17].…”
Section: Interface Energeticsmentioning
confidence: 99%